PENGEMBANGAN DESAIN DIDAKTIS PERSAMAAN LINEAR SATU VARIABEL (PLSV) PADA PEMBELAJARAN MATEMATIKA MTsN MODEL CIGUGUR - Dani Hidayat; Uba Umbara; Evan Farhan Wahyu Puadi (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2016)
Mathematic learning problem occur by students because there are learning obstacle in student self. The obstacle is based on didactical obstacle is the less teacher competence in managing dan preparing of learning process and epistimological obstacle, that is beginning knowledge student which can’t be applied in another condition. Therefore, this didactical design research is used as effort to exceed learning obstacle which is felt by student. This research is didactical design research with descriptive quality method use design research is Didactical Design Research (DDR). Data collecting method for this research is question, interview, literature study, and observation. This research held in MTsN Model Cigugur Kuningan at class VII.1 and VII.3. From this research carried out some learning obstacle are 1) epistimological obstacle because student mistake in operating algebra operation and difficulty in intrepreting story problem to model and applied mathematic form, 2) ontogenikal obstacle because the limitedness student in abstract thinking 3) didactical obstacle because the teacher jus using teacher center approach